(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research aims to explain the fields of the legal endowment in Islamic history and civilization, and how these fields expanded from the era of the Prophet hood until our present time, and to explain the reason for this expansion and its benefit, and the main research problem in the case of the endowment in Islamic history and its development, and the reason for its expansion throughout history from the era of the honorable companions until the modern era. The researcher followed the analytical inductive method, so he read the history books and extracted what is related to the endowment, especially with regard to the fields of the endowment and the people working in it, then analyzed the reason for the expansion and indicated the importance of this expansion in serving Islamic law and its purposes. This research led to several results, the most prominent of which are: A project with its origin in Islamic law, and that it is one of the best alms, and that the companions and those after them cared greatly in having endowments for them to benefit from their reward after death, and that the successor of this nation followed what was on its predecessor in the continuity of the endowment and urging it, as well as the fields of endowment expanded in Islamic history until Al Waqf included new areas in almost every era.